'Print is Much Safer than MS': The Fate of Folklore and Folk Song Collections in the Isle of Man. Issue 1 (29th November 2018) - Miller, Stephen
The Isle of Man in the 1890s saw remarkable activity in the collecting of folklore and folk song, both in English and Manx Gaelic. This was followed by a further wave of collectors in the next decade, enthused by the Celtic Revival. Much of the material collected has now been lost for a variety of reasons detailed in this article. The most significant loss was that of the cylinder recordings made by the Manx Language Society between 1905 and 1913. Several collectors expressed concern in their lifetime about the survival of their papers, but this did little to prevent the loss of the collections they amassed. Such a fragmented record has consequences in researching what does now survive.